Cost Analysis of the Construction Safety Management System (SMKK) Based on Work Breakdown Structure (WBS) in an Irrigation Project - Syarif, Husein; Machfudiyanto, Rossy Armyn (Journal of Project Management Research, 2025)
Infrastructure development, particularly water infrastructure such as irrigation channels, plays a crucial role in regional development. In its implementation, construction safety becomes a critical aspect. The Construction Safety Management System (SMKK), as regulated in the Indonesian Ministry of Public Works and Housing Regulation No. 10 of 2021, serves as a guideline for ensuring safety in construction projects. One of the key components of SMKK is the accurate cost planning based on risk control programs for each activity, analyzed through a Work Breakdown Structure (WBS) approach. This research aims to develop a cost estimation of the SMKK using a Work Breakdown Structure (WBS)-based approach tailored to irrigation construction projects. The research includes identifying detailed work packages and activities, analyzing potential hazards and risks, formulating occupational health and safety (OHS) objectives and programs, and estimating SMKK costs in a case study of the DI. Saddang Irrigation Rehabilitation Project. The results provide a structured WBS framework, a comprehensive risk profile, and an estimated SMKK cost distribution, in which the largest portion is allocated to safety personnel, followed by training, personal protective equipment, and insurance.